The Role of Vimentin in the YAP signaling in Wound Healing and Cancer Invasion - Ansari Asl, Afshin (My University, 2023)
Vimentin, a crucial cytoskeletal protein, plays a role in wound healing and cancer progression. However, its precise mechanism is not fully understood. Previous research has shown a connection between the expression levels of YAP, a component of the Hippo pathway, and vimentin. Studies on Vim -/- mice revealed a delay in the activation of the TGF-β1 pathway, impacting downstream signaling including SMAD3 and ERK. Considering the above information and the dependence of YAP on phosphorylation for YAP-shuttling, two experiments were conducted to enhance understanding and validate the proposed mechanism. 2D Human Dermal Fibroblast (HDF) cell cultures were employed. Calyculin A was applied to assess the phosphorylation-dependency of YAP shuttling in our model. In another experiment, two YAP mutants were transfected in HDF cells to examine the role of vimentin in YAP-shuttling. We demonstrated that treatment of cells with Calyculin A, a protein phosphatase inhibitor, can influence YAP localization. Calyculin A also caused the phosphorylation of SMAD3. While YAP-shuttling was disrupted in Vim -/- cells after exposure to Calyculin A. On the other hand, transfection of YAP WT plasmid in vimentin WT HDF cells resulted in the overexpression of YAP levels, but no differences were observed after transfection with the same plasmid in Vim -/- cells, indicating a possibility where vimentin regulates the upstream YAP-shuttling process. These findings provide insights into the crucial role of vimentin in wound healing and cancer progression through its interaction with YAP1, highlighting its significance in regulating gene expression and promoting the proliferation of cancer cells.
Keywords: YAP-shuttling, vimentin, protein phosphatase inhibitor, YAP WT plasmid, wound healing, cancer invasion